Prevalence of general and abdominal obesity in 2015–2016 and 8-year longitudinal weight and waist circumference changes in adults and elderly: the Tromsø Study - Løvsletten, Ola; Jacobsen, Bjarne Koster; Grimsgaard, Sameline; Njølstad, Inger; Wilsgaard, Tom; Løchen, Maja-Lisa; Eggen, Anne Elise; Hopstock, Laila Arnesdatter (BMJ Open, 2020)
Objectives - To describe the prevalence of general (body mass index (BMI) ≥30 kg/m2) and abdominal (waist circumference women >88 cm, men >102 cm) obesity in Tromsø 7 (2015–2016), and the secular change from Tromsø 6 (2007–2008). Furthermore, to study longitudinal changes in body weight and waist circumference from Tromsø 6 to Tromsø 7. Setting - A population study in Tromsø, Norway. Participants - The cross-sectional analyses included 20 855 participants in Tromsø 7 (aged ≥40 years) and 12 868 in Tromsø 6 (aged ≥30 years). The longitudinal analyses included 8592 participants with repeated measurements, aged 35–79 in Tromsø 6. Outcome measures - Mean age-specific and sex-specific BMI, waist circumference, prevalence of general and abdominal overweight and obesity, as well as longitudinal changes in body weight and waist circumference according to sex and birth cohort. Results - Over 8 years, the age-adjusted prevalence of general obesity increased (p<0.0001) from 20.1% to 23.0% in women and from 20.7% to 25.2% in men. The age-adjusted prevalence of abdominal obesity did not increase in women (from 54.7% to 53.4%), and the increase in men was modest (from 36.8% to 38.6%, p=0.003). Longitudinal analyses showed an increase in body weight, by 1.1 kg (95% CI 0.9 to 1.2) in women and 0.7 kg (95% CI 0.6 to 0.9) in men, and also waist circumference, by 1.3 cm (95% CI 1.0 to 1.5) in women and 1.4 cm (95% CI 1.2 to 1.6) in men. There were inverse relationships (p<0.001) between age at baseline and change in weight and waist circumference. Conclusions - Repeated cross-sectional analyses showed that the prevalence of general obesity increased, whereas the increase in abdominal obesity was less marked. Longitudinal analyses showed increases in both body weight and waist circumference. The youngest age groups have the largest increase.